Bloempje, kostuumpje, wieltje of bloemetje, kostumetje, wieletje? Een corpusanalyse naar de Nederlandse diminutieve allomorfie - Gőcze, Borbála (Acta Neerlandica, 2024)
This article deals with the variation of diminutive forms in contemporary Standard Dutch. Despite the well-described rules of diminutive formation, there are a number of words that have more than one well-formed diminutive forms in Dutch. The article provides a brief overview of diminutive formation in Dutch, as well as a description of the cases where a word can have more than one grammatical diminutive form. The second part of the article is an account of a corpus-based study examining the words that contain a high vowel in their final (or only) syllables and end in m, n or l. The goal of the study is to examine the behaviour of the diminutive forms of these stems.